Preaching that changes lives - Fabarez, Michael, 1964- (Nashville, Tenn. : T. Nelson Publishers, 2002)
Mike Fabarez contends persuasively that unless a sermon makes a difference in the lives of its hearers, the preacher and the congregation have missed the point. No matter how much information is communicated, unless application is central throughout the message, the sermon has failed to be biblical. In fifteen brief chapters, the author demonstrates how the goal of changing lives can permeate the planning, preparation, presentation, and pastoral follow-through of every sermon. And in the process, the preacher's life will be changed too.
Part 1 : rethink your task -- Understand the life changing power of preaching -- Adopt a life changing method of preaching -- Part 2 : prepare to change lives : make sure your life is changing -- Study your passage and your audience with life change in mind -- Frame an outline that will change you audience -- Pray pray pray for a sermon that will change lives -- Come to grips with the time it takes to prepare a life changing sermon -- Part 3 : preach to change lives -- Realize they won't change what they don't hear and understand -- Keep the life changer at the center of your sermon -- Preach change with authority -- Give them more than the bottom line -- Preach periodically about life changing preaching -- Part 4 : follow through to change lives : cultivate a culture of commitments and accountability -- Provide tools to help your audience make specific changes -- Personally model the changes from last week's sermon.
Includes bibliographical references (pages 222-224).
Keywords: Preaching